Characteristics of heat and water resources allocation and utilization in rice-rice/re-rape triple cropping systems in Southern China - Xiaohua Bian; Zhan Jiang; Yifan Cao; Fangyuan Huang; Bo Duan; Xiaolu Xiao; Ni Ma (Journal of Agriculture and Food Research)
Crop rotation is a cultivation system that utilizes the growth and ecological requirements of different crops on the same fields. The rice-rice/re-rape rotation system is a sustainable agricultural model, yet challenges persist due to field occupation conflicts between crops. To improve the rotation system, the heat and water resource allocation patterns across six experimental sites in Southern China are analyzed and guidance for triple rotation system cultivation is proposed. Results indicate that a 180-day period in the field for either rice or rapeseed is the key point to establishing triple cropping system in Southern China. Moreover, the growth periods of rice and rapeseed in south of 27°N already meet the requirements for triple cropping production, and efforts should be made to improve yield and income, particularly in Liuzhou. However, it is necessary to shorten the growth period of rapeseed in regions between 27°N and 30°N to achieve a seamless annual transition. Therefore, conducting cultivation technology research based on field trials in different regions will be of great significance for optimizing grain-oil production and advancing sustainable agriculture in China.